Thalamic bacterial abscess presenting with hemiparesis and expressive aphasia. (2018) - Hernandez Jimenez, Jarelys M.; Vahdat, Kelia; Serrano Santiago, Ivan A.; Morales Hernandez, Maria del Mar; Isache, Carmen L.; Sands, Michael
Abstract: Brain abscesses are relative rare in the developing world, with an incidence of 2% of all space occupying lesions. Deep-seated abscesses such as thalamic and basal ganglia abscesses are much rarer than abscesses in other locations of the brain, comprising 1.3–6% of all brain abscesses. These abscesses may present with hemiparesis, and subcortical aphasia has only been reported in a few cases throughout the literature. Here we present and discuss a case of thalamic brain abscess caused by S. anginosus that presented with subcortical aphasia.